2018
DOI: 10.1016/j.paid.2018.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Are non-verbal facial cues of altruism cross-culturally readable?

Abstract: Although both dynamic (i.e., facial expressions) and static facial traits are used as cues of altruism, only static facial traits have been shown to be cross-culturally readable with respect to altruism detection skills. To investigate whether dynamic facial cues of altruism are also cross-cultural, we asked French subjects to estimate the altruism of Japanese individuals on the basis of silent video clips. These video clips were taken from a previous experiment, which found that Japanese raters were able to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…This means that Japanese people need to pay more attention to subtle, difficult-to-control movements around the eyes. Indeed, one study revealed that French participants were unable to correctly estimate the altruism level of videotaped Japanese targets using the same stimuli in this study (Tognetti et al 2018). This may be explained by the French participants, who relied more on lower facial parts, not having enough altruistic cues in the Japanese targets.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…This means that Japanese people need to pay more attention to subtle, difficult-to-control movements around the eyes. Indeed, one study revealed that French participants were unable to correctly estimate the altruism level of videotaped Japanese targets using the same stimuli in this study (Tognetti et al 2018). This may be explained by the French participants, who relied more on lower facial parts, not having enough altruistic cues in the Japanese targets.…”
Section: Discussionmentioning
confidence: 56%
“…This may be explained by the French participants, who relied more on lower facial parts, not having enough altruistic cues in the Japanese targets. To be precise, Tognetti et al (2018) did not use the Faith game to measure participants' evaluation of altruism in the targets. Therefore, it is possible that it was methodological, not cultural, differences that brought about the differences in results.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals' assessments and decisions regarding a cooperative other rely on facial cues, including width-to-height ratio (Little, Jones, DeBruine, & Dunbar, 2013;Stirrat & Perrett, 2010 and the presence of a genuine (i.e., Duchenne) smile (Brown, Palameta, & Moore, 2003;Centorrino, Djemai, Hopfensitz, Milinski, & Seabright, 2015;Johnston, Miles, & Macrae, 2010;Oda, Naganawa, Yamauchi, Yamagata, & Matsumoto-Oda, 2009;Reed, Zeglen, & Schmidt, 2012). In addition, facial cues of cooperativeness are reliable and valid across cultures (Tognetti, Berticat, Raymond, & Faurie, 2013;Tognetti, Yamagata-Nakashima, Faurie, & Oda, 2018).…”
mentioning
confidence: 99%
“…In our setting, the cultural proximity of experimental samples (drawn from student populations in major French cities) naturally satises this requirement. However, recent evidence by Tognetti et al (2018) suggests that increasing the cultural distance between the interaction parties may aect the predictive value of non-verbal content, making it more useful within cultural proximity than across cultures. A natural question to ask is whether the rationality of preferences for observable information would persist in an inter-cultural setting.…”
Section: W T Avmentioning
confidence: 99%